Analysis of the influence of volleyball learning and motor skill son the basic concept of volleyball - Ridho, Faizal; Wahyuni, Dewi; Nurbait, Syifa (Universitas Tanjungpura, 2022)
This study aims to analyze the influence of volleyball learning and motor skills on the understanding of the basic concepts of volleyball games in Nuruddin Tonjong Junior High School students. The background of this research is based on the importance of physical education, especially the sport of volleyball, in developing students' motor and cognitive skills from school age. This study uses a quantitative approach with survey methods and regression analysis. The research population is all grade IX students of Nuruddin Tonjong Junior High School for the 2022/2023 school year as many as 45 people, which is also a sample with total sampling techniques. The data collection instrument uses a closed questionnaire that has been tested for validity and reliability. The results of the analysis showed that learning volleyball sports and motor skills partially or simultaneously had a significant effect on mastering the basic concepts of the game of volleyball. Thus, structured volleyball learning and improving students.